Evaluasi Layanan Buku Elektronik (E-Book) oleh Pemustaka di Perpustakaan Kementerian Pendidikan Dasar dan Menengah (Kemendikdasmen) - Novi Arikha Rahmadani; Jazimatul Husna (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Digital transformation has encouraged libraries to develop technology-based services, including electronic book (e-book) services. The Library of the Ministry of Primary and Secondary Education (Kemendikdasmen) has implemented an e-book service to improve access to information for its users. However, the utilization of this service has not been comprehensively evaluated from the users' perspective. This study aims to evaluate the e-book service by examining its utilization level, usage patterns, and factors influencing its use. A qualitative descriptive approach was employed through in-depth interviews, observation, and documentation. The informants consisted of active users of the Kemendikdasmen Library e-book service. Data were analyzed using data reduction, data display, and conclusion drawing, while source triangulation was applied to ensure data validity. The findings indicate that the e-book service has been utilized to support educational, professional, and information needs. Usage patterns are primarily driven by users' information requirements, while utilization is influenced by accessibility, collection availability, users' digital literacy, and service promotion. Nevertheless, several challenges remain, including low usage intensity, limited understanding of application features, and insufficient service promotion. Therefore, improving digital collections, enhancing application features, and strengthening promotional strategies are necessary to optimize the utilization of e-book services.